Swiss franc currency regime after the global financial crisis - Finkelshtein, Ekaterina; Brůna, Karel, 1973-; Šímová, Kateřina; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2020)
Switzerland is known for being a country with stable pollical and economic climate, whose currency is therefore regarded as a ‘safe haven’ by many foreign investors. In times of the global financial and the following Eurozone crises, the monetary authority had not only to deal with the aftermath of global markets’ disruptions, but also to protect the country’s currency against rapid appreciation. For this reason, a minimum exchange floor was enacted by SNB in September 2011. However, in 2015 it suddenly decided to discontinue the CHF/EUR threshold, which caused a profound effect on the markets. This Thesis’s goal is to examine and analyze the Swiss franc currency regime since the start of the global financial crisis. The first theoretical background chapter researches the methodology and classification of the currency regimes in connection to the monetary policy. Next chapter documents and evaluates the SNB’s responses during various stages of the crises. The practical part studies the monetary policy decisions by observing data and using available indicator tools. Finally, the results of all chapters are compared, and a concluding opinion is reached.
Vedoucí práce: Karel Brůna
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses